Cultura de segurança do paciente na atenção primária à saúde - Souza, Marina Mazzuco de (2017)
This study aimed to evaluate the patient's safety culture in the Primary Health Care of a city in the central-western region of the State of Rio Grande do Sul, Brazil. Cross-sectional study, conducted in 2016, with health professionals working in Primary Health Care in the city of Santa Maria / RS. To evaluate the safety culture, the Brazilian version of the Safety Attitudes Questionnaire Ambulatory Version (SAQ-AV) was used, as well as complementary questions for sociodemographic and occupational characterization of the participants. The data were organized in the Epi-Info® program, version 6.4, and analyzed in the PASW Statistics® program. SAQ-AV was measured by the total score and its nine domains. Positive safety attitudes were considered scores ≥7.5. 254 professionals from the 28 health services (Basic Health Unit, Strategy and Family Health, mixed units and management) participated. Female workers predominated (81.1%); Aged between 22 and 39 years (53.6%); Married or living with a partner (65%); Who worked in FHS (44.1%), had a mixed shift (84.6%); Worked for over 13 years (36%); They did not have another job (78.7%); They liked their job (97.2%); The form of contact with the direct patient (96.1%). The SAQ-AV score varied between 3.4 and 8.4 with a mean of 7.0 (± 9.3). The internal consistency of SAQ-AV was 0.86. Positive evaluation was only seen in the Patient Safety domain. Total SAQ-AV presented a significant difference for positive culture in the perception of Nursing Technicians and professionals of the Family Health Strategy. The domain Satisfaction in the Work was significant for positive culture in the professional categories of Nursing Technicians, Community Health Agent, Doctors and Nursing Assistants, and the Communication presented higher percentages of positive evaluation by Nursing Technicians. Among the professional categories, only the Community Health Agents were classified with positive culture in the Permanent Education field. Professionals aged between 40 and 63 years had significantly higher percentages for low recognition of stress. Participants cited suggestions for improving patient safety that have been grouped into: Patient Safety Protocols in Primary Health Care; Training; Work Environment and Infrastructure; Conditions and Work Overload; Communication; Error; Resolutivity. It is concluded that the safety culture in the Primary Health Care environment researched needs to be carried out. Strengthening Health Care Networks, building partnerships, engaging patients in care, discussing and discussing patient safety among staff and in the context of institutional reality are important steps for the safety culture to be solidified.